A Functional Neuroimaging Analysis of the Trail Making Test-B: Implications for Clinical Application - Mark D. Allen; Tyler E. Owens; Alina K. Fong; Douglas R. Richards (Behavioural Neurology)
Recent progress has been made using fMRI as a clinical assessment tool, often employing analogues of traditional “paper and pencil” tests. The Trail Making Test (TMT), popular for years as a neuropsychological exam, has been largely ignored in the realm of neuroimaging, most likely because its physical format and administration does not lend itself to straightforward adaptation as an fMRI paradigm. Likewise, there is relatively more ambiguity about the neural systems associated with this test than many other tests of comparable clinical use. In this study, we describe an fMRI version of Trail Making Test-B (TMTB) that maintains the core functionality of the TMT while optimizing its use for both research and clinical settings. Subjects (N = 32) were administered the Functional Trail Making Test-B (f-TMTB). Brain region activations elicited by the f-TMTB were consistent with expectations given by prior TMT neurophysiological studies, including significant activations in the ventral and dorsal visual pathways and the medial pre-supplementary motor area. The f-TMTB was further evaluated for concurrent validity with the traditional TMTB using an additional sample of control subjects (N = 100). Together, these results support the f-TMTB as a viable neuroimaging adaptation of the TMT that is optimized to evoke maximally robust fMRI activation with minimal time and equipment requirements.